The Effect Of Results Share Level, Third Party Funds, Non Performing Financing On Results-Based Financing Volume In Sharia Banking In Indonesia - Kamaruddin, Kamaruddin; Wahyudi, Akhmad; Gani, Ilham (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
This study aims to determine the effect of Profit Sharing, Third Party Funds and Non-Performing Financing on Profit Sharing-Based Financing Volume at Islamic Banks in Indonesia in 2016-2020. This type of research uses quantitative research. The population used in this study are all Islamic commercial banks in Indonesia that are registered with the Financial Services Authority (OJK) and have the financial ratios required in the study.sampling technique used was purposive sampling. By taking a sample of 7 banks. Data processing and analysis techniques in this study are using the Classical Assumption Test and Hypothesis Testing. The results of this study indicate that the level of profit sharing and third party funds have a positive and significant effect on the volume of profit-sharing-based financing and non-performing financing has no effect on the volume of profit-sharing-based financing. Then the level of profit sharing, third party funds and non-performing financing simultaneously affect the volume of profit-sharing based financing.